Diep snydende vrae, met antwoorde gebore uit weerloosheid Nav Jurie le Roux se 'spirituele empatie' - Veldsman, Dani P. (2013)
Deep probing questions but answers conceived in vulnerability: On Jurie le Roux’s ‘spiritual empathy’. Taking the conversation between the Old Testament scholar Jurie le Roux and the dogmatician Johan Heyns as point of departure, it is argued that his well-founded criticism of Heyns has to be taken seriously, as well as his proposition in favour of spiritual empathy to enhance the understanding of historical texts. However, his recommendation for spiritual emphaty is subsequently constructively valued and criticised from a theological-experiential perspective. It is especially noted that, on the one hand, Le Roux’s reactionary historical point of view regarding, amongst others, the retrieval of the orginal intention of the author/text is convincing. On the other hand, it is argued that his perspective is predisposed toward an unproblematical self in the present. As a result, the act of historical interpretation is reduced to dependence on ‘the seams of the heart’ in the individual quester. It is after all argued and substantiated from systematic-theological, postmodern, philosophical and theological-scientific perspectives that historicity does not consist solely of historical ‘seeing’ in the sense of retaining the original intention of the author. Historical understanding also entails historical ‘hearing’ (that is, a surplus of meaning) which broadens and enriches historical understanding.
Keywords: Historical understanding; Johan Heyns; Jurie Le Roux; Spiritual Empathy